2017
DOI: 10.1007/s12630-017-0973-2
|View full text |Cite
|
Sign up to set email alerts
|

The effect of simulator fidelity on acquiring non-technical skills: a randomized non-inferiority trial

Abstract: This study suggests that low-fidelity simulators are non-inferior to the more costly high-fidelity simulators for teaching NTS to postgraduate medical trainees.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…In the case of simulation-based learning experiences as an example of EL, the level of realism or trueness to which they replicate or resemble the ‘real world’, known as fidelity (Gu et al, 2017 ), has been a topic for debate. While both low and high fidelity simulations were effective in improving procedural skill performances (Lefor et al, 2020 ), studies have shown that this might not always be the case, particularly when examining non-technical skill acquisition (Gu et al, 2017 ; Lefor et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the case of simulation-based learning experiences as an example of EL, the level of realism or trueness to which they replicate or resemble the ‘real world’, known as fidelity (Gu et al, 2017 ), has been a topic for debate. While both low and high fidelity simulations were effective in improving procedural skill performances (Lefor et al, 2020 ), studies have shown that this might not always be the case, particularly when examining non-technical skill acquisition (Gu et al, 2017 ; Lefor et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In the case of simulation-based learning experiences as an example of EL, the level of realism or trueness to which they replicate or resemble the ‘real world’, known as fidelity (Gu et al, 2017 ), has been a topic for debate. While both low and high fidelity simulations were effective in improving procedural skill performances (Lefor et al, 2020 ), studies have shown that this might not always be the case, particularly when examining non-technical skill acquisition (Gu et al, 2017 ; Lefor et al, 2020 ). A 2017 review on the effects of fidelity on non-technical skill acquisition revealed no significant difference between low and high fidelity simulators, suggesting that low fidelity EL is as effective as high fidelity for teaching non-technical skills (Gu et al, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…11 Low-cost simulation is recognised as valid for learning non-technical skills in high-and low-income settings. 13,26 Education in low-resource settings requires 'contextually informed tools' to teach and assess non-technical skills. 10 The VAST course was designed de novo, stemming from a long-standing partnership between the University of Rwanda and Dalhousie University.…”
Section: Discussionmentioning
confidence: 99%
“…34,35 For the development of non-technical skills, low-cost simulators have been shown to be non-inferior to high-cost simulators. 26 The elements of simulation training that promote effective learning are repetitive practise, provision of feedback, and curriculum integration. 36 Factors, such as emotional fidelity, are not reliant on high-cost equipment.…”
Section: Discussionmentioning
confidence: 99%
“…The psychomotor technical hands‐on interaction between learner, simulator, and instructor potentially has very different educational objectives than the learning that takes place in a context focused clinical scenario simulation . It is not surprising that using complex, high‐fidelity manikins for a simulation exercise meant to assess nontechnical skills is not likely to add value . While these high‐tech, expensive manikins may talk, blink, and accommodate various procedures, these feature‐rich actions are often not very realistic and have the potential to distract participants from the intended learning objectives of the simulation .…”
Section: How Real Does Simulation Need To Be?mentioning
confidence: 99%